2017
DOI: 10.1530/jme-17-0026
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell senescence: role of IL-6 in the pituitary

Abstract: IL-6 is a pleiotropic cytokine with multiple pathophysiological functions. As a key factor of the senescence secretome, it can not only promote tumorigenesis and cell proliferation but also exert tumor suppressive functions, depending on the cellular context. IL-6, as do other cytokines, plays important roles in the function, growth and neuroendocrine responses of the anterior pituitary gland. The multiple actions of IL-6 on normal and adenomatous pituitary function, cell proliferation, angiogenesis and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 163 publications
2
19
0
Order By: Relevance
“…hBTSCs cultured under chronic exposure of cholest-4,6-dien-3-one showed significantly higher IL6 levels (3.05 ± 0.69 pg/mL; p < 0.001; N = 6) when compared to hBTSCs culture in basal condition (0.94 ± 0.11 pg/mL; N = 6) (Figure 2B). As observed in previous studies [28,29,30], our data suggest that high IL6 levels induce cell senescence in hBTSC cultures when cultured in KM supplemented with cholest-4,6-dien-3-one.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…hBTSCs cultured under chronic exposure of cholest-4,6-dien-3-one showed significantly higher IL6 levels (3.05 ± 0.69 pg/mL; p < 0.001; N = 6) when compared to hBTSCs culture in basal condition (0.94 ± 0.11 pg/mL; N = 6) (Figure 2B). As observed in previous studies [28,29,30], our data suggest that high IL6 levels induce cell senescence in hBTSC cultures when cultured in KM supplemented with cholest-4,6-dien-3-one.…”
Section: Resultssupporting
confidence: 90%
“…Here we showed increased interleukin 6 (IL-6) production and secretion in hBTSCs in vitro. In previous studies, a strong link between IL-6 secretion and senescence was demonstrated [28,29,30]. One of the limitation of our study is the lack of a detailed analysis of the SASP profile of cells treated with cholest-4,6-dien-3-one and untreated ones.…”
Section: Discussionmentioning
confidence: 91%
“…In GH3 cells, IL-6 stimulates cell proliferation and DNA synthesis, as well as GH and prolactin release (Arzt et al 1993). IL-6 can also be secreted by non-tumoural folliculo-stellate cells, which can have paracrine effect on pituitary tumour cells causing increased proliferation and aggressiveness (Renner et al 1998, Haedo et al 2009, Sapochnik et al 2017a. Our study shows that TAFderived IL-6 levels were higher in PitNETs with cavernous sinus invasion, supporting a possible role for the paracrine effects of IL-6 on pituitary tumour invasiveness.…”
Section: Figuresupporting
confidence: 62%
“…Moreover, persistent SASP may help tumour cells to migrate and invade (Coppe et al 2008, Tammela et al 2017. It was also demonstrated that endogenous IL-6, as a SASP component, and hormone secretion (Chesnokova et al 2013, Sapochnik et al 2017 underlie the senescence-associated slow proliferation rate and benign nature of pituitary tumours. In contrast, other evidence indicates that senescence and pituitary stem cell associated persistent activation of SASP drive paracrine NF-κB in senescence of pituitary tumours B Mongi-Bragato et al…”
Section: Discussionmentioning
confidence: 99%